1990
DOI: 10.1002/jbm.820241105
|View full text |Cite
|
Sign up to set email alerts
|

Poly(anhydride) administration in high doses in vivo: Studies of biocompatibility and toxicology

Abstract: Poly(anhydrides) proposed for use as vehicles for controlled drug delivery were administered subcutaneously in Sprague-Dawley rats at two dosage levels (800 mg/kg rat and 2400 mg/kg rat) for a period of eight weeks. Biocompatibility was assessed using a number of methods. Thirty-six clinical chemistry and hematology parameters were monitored throughout the study. Blood values were statistically analyzed for any possible effects due to the implanted polymer. After 8 weeks, rats were sacrificed and complete necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
1
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 9 publications
0
43
1
1
Order By: Relevance
“…Molecular (18). The polyanhydrides after purification (12) were frozen in liquid nitrogen, micronized in a Technilab micromill (Baxter Scientific Products, McGaw, IL), and sieved to 130-150 ,um.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular (18). The polyanhydrides after purification (12) were frozen in liquid nitrogen, micronized in a Technilab micromill (Baxter Scientific Products, McGaw, IL), and sieved to 130-150 ,um.…”
Section: Methodsmentioning
confidence: 99%
“…However, the polymers used for such delivery are limited to those that are inert toward the incorporated proteins-i.e., those polymers that neither bind to irreversibly nor promote decomposition of the proteinaceous therapeutic agent. Polyanhydrides have been investigated in our and other laboratories as biodegradable implants (10)(11)(12). Furthermore, polyanhydrides are one of the few synthetic biodegradable polymers being studied clinically as injectable or as implantable matrices.…”
mentioning
confidence: 99%
“…Tissue reactions and toxicological studies showed that polyanhydrides were biocompatible. 13,14 For example, they are currently used in clinics to deliver BCNU (carmustine, 1,3-bis [2-chloroethyl]-1-nitro-sourea) locally within the brain to treat patients with brain tumors. 15 However, it is difficult, if not impossible, to keep the surface area of a bulk polyanhydride sample constant during the erosion except for a very thin film.…”
Section: Introductionmentioning
confidence: 99%
“…Polyanhydrides are biocompatible and degrade in vivo into nontoxic dicarboxylic acids in predictable rates and patterns counterparts that are eliminated from the body as metabolites. Recent studies on polyanhydrides as drug carriers show that the anhydrides degrade in a controlled fashion and are biocompatible with the human body tissues including the brain [1,2] .…”
Section: Introductionmentioning
confidence: 99%